The Relationship Between Negative Life Events and Internet Addiction Disorder Among Adolescents and College Students in China: A Systematic Review and Meta-Analysis - Wang, Jun; Hao, Qing-hong; Tu, Yang; Wang, Yang; Peng, Wei; Li, Hui; Zhu, Tian-min (Frontiers in Psychiatry, 2022)
Objective Internet Addiction Disorder (IAD) has become a social problem. Literature suggests that negative life events can cause numerous problematic behaviors and part of them will result in IAD. However, there is a lack of evidence that elucidates the association between negative life events and IAD. Thereby, we performed a comprehensive analysis to further document the relationship between negative life events and IAD among adolescents and college students in China. Methods We searched ten electronic databases for relevant articles. We extracted correlation coefficient (r) values from each study and calculated 95% confidence interval (95% CI) after applying Fisher’s z. A random-effect or fixed-effect model was applied to analyze the data. Heterogeneity was examined using I2 statistics and the Cochran’s Q statistics. Results A total of 31 studies were involved in this meta-analysis. Positive correlation was observed between negative life events and IAD. The subtype interpersonal relationship of negative life events was closely associationed with IAD. Conclusion There were significant positive association between negative life events and IAD. The findings can be used to guide IAD interventions. Systematic Review Registration [https://www.crd.york.ac.uk/prospero/#recordDetails].